The p−n junction under nonuniform strains: general theory and application to photovoltaics. (January 2018) - Guin, L.; Jabbour, M.E.; Triantafyllidis, N.
Abstract: It is well known that mechanical strains influence the electronic properties of semiconductor devices. Modeling the fully coupled mechanical, electrical, and electronic responses of semiconductors is therefore essential for predicting the effects of mechanical loading on their overall electronic response. In the first part of this paper, we develop a general continuum model that couples the mechanical, electrical, and electronic responses of a finitely deformable semiconductor. The proposed model accounts for the dependence of the band edge energies, densities of states, and electronic mobilities on strain. The governing equations are derived from the basic principles of the thermomechanics of electromagnetic continua undergoing electronic transport. In particular, we find that there exists electronically induced strains that can exceed their electromagnetic (Maxwell) counterparts by an order of magnitude. In the second part, motivated by applications that involve the bending of a photovoltaic cell, we use asymptotic methods to compute the current–voltage characteristic of a p − n junction under nonuniform strains. We find that, for a typical monocrystalline silicon solar cell, the changes in dark current are significant, i.e., of the order of 20% for strains of 0.2%.